Agroforestry in Arid Regions for sustainable livelihoods - Roy, M. M.; Tewari, J. C. (Indian Farming, 2015)
Agroforestry systems combining tree/shrub, crop, grass and livestock have great scope and role in optimizing land productivity and environmental protection in the fragile ecosystems. Agroforestry with suitable tree species in different arid land forms thus assumes much significance for desertification control and ecosystem services as well. Agroforestry that is traditionally followed in these regions is a complete, ecologically sustainable livelihood system. To meet both present and future demands, policies need to be supportive of the development of such traditional agroforestry systems based on synergism with nature. Vigorous adoption of agroforestry in the region is recommended for maintenance of productivity and sustainability in this region. The characteristics of trees which are generally considered to be environmentally beneficial are on account of their ability to utilize incoming solar radiation throughout the year; to enrich micro sites by depositing litter in the topsoil for its subsequent utilization by crops/grasses; to modify the microclimate, which can bring about favorable effect on the soil and associated plant species. The appropriate combination and management of tree/shrub (both forest and fruit), crops, grasses and livestock units (in mixed herds) will open up more opportunities for livelihood on a sustainable basis.